2016
DOI: 10.1016/j.plefa.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Association between breast milk fatty acids and HIV-1 transmission through breastfeeding

Abstract: A residual mother-to-child transmission of HIV through breastfeeding persists despite prophylaxis. We identified breast milk fatty acids (FA) associated with postnatal HIV transmission through breastfeeding in a case-control study. Cases (n=23) were HIV-infected women with an infant who acquired HIV after 6 weeks of age. Controls (n=23) were matched on infant׳s age at sample collection. Adjusting for maternal antenatal plasma CD4 T cell count, cis-vaccenic acid (18:1n-7) and eicosatrienoic acid (20:3n-3) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…All three n6 PUFAs; linoleic, DGLA and AA, were shown to have similar protective potency in vitro [ 10 ]. However, this protective effect of n6 PUFAs was not found by Badiou et al [ 24 ]. We did not find a statistically significant relationship between the mean proportion of the essential n6 PUFA linoleic acid and the health of the mother, infant, or both.…”
Section: Discussionmentioning
confidence: 72%
“…All three n6 PUFAs; linoleic, DGLA and AA, were shown to have similar protective potency in vitro [ 10 ]. However, this protective effect of n6 PUFAs was not found by Badiou et al [ 24 ]. We did not find a statistically significant relationship between the mean proportion of the essential n6 PUFA linoleic acid and the health of the mother, infant, or both.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, inflammation in breast milk interplays with breast milk fatty acid profile. Hence, we recently observed that IL15, IP10, and β2 microglobulin, correlate positively for cis-vaccenic acid, and negatively for eicosatrienoic acid in breast milk collected from HIV infected mothers [26].…”
Section: Discussionmentioning
confidence: 90%
“…IL-8 is a chemokine produced by macrophages and epithelial cells, both of which are an important fraction of the breast milk cellular composition [11]. IL-8 is a major mediator of the inflammatory response 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 collected from HIV infected mothers [26].…”
Section: Discussionmentioning
confidence: 99%
“…When D6D is less active than elongase 5 the amount of ETE in breast milk increases. A higher concentration of ETE was associated with a lower risk of HIV-1 transmission [213]. Unfortunately, a large prospective cohort study is still lacking in this matter.…”
Section: Role Of Unsaturated Fatty Acid Desaturases In Humans and Othmentioning
confidence: 98%